The G20: its role and challenges - Kathrin Berensmann; Thomas Fues; Ulrich Volz (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Global politics were recently graced with a new, influential steering committee. Since the global financial crisis, the leaders of the 19 most important industrial and emerging countries, as well as the EU, have been striving to stabilize the world economy. Nevertheless, there are many questions about their endeavours: What authorises the G20 to take a leadership role? What influence do emerging countries have on overall concepts regarding development policy? Are the members of this new group of states primarily interested in advancing their national goals, or are they also acting for the global common good? Because the G20 represents only part of the world's population and a good 173 countries are not members, ways should be found to include the latter's concerns. On a positive note, it should be mentioned that the G20 is increasingly seeking to dialogue with developing countries. This occurs through invitations of regional organisations such as the Association of Southeast Asian Nations (ASEAN) and the African Union to G20 summits and individual members' advisory processes with neighbouring states. But the G20 is still just beginning to open itself to the concerns of civil society forces and non-governmental organisations. Thusfar, the results of the G20's development policy have been very mixed. On one hand, the equal participation of up-and-coming powers of the Global South such as China, India, Brazil and South Africa ensures that issues of global development are coming into focus. On the other hand, there is a danger that emerging countries will not be ready to make any adjustments to their development paths in the name of future viability. The decisions at the G20 summit in South Korea in November 2010 point in this direction. In principle, the G20's adoption of a development policy programme that focuses on the development friendly design of global economic parameters is to be welcomed. But the Seoul Development Consensus's one-sided emphasis on growth portends regression for the international development agenda because issues of environmental sustainability are not addressed. In preparation for the Rio+20 summit in 2012, it would be wise for the G20 to reorient itself and campaign for the climate- and environmentally-safe transformation of the world economy, instead of backing resource-intensive production and consumption patterns that already unduly strain global ecosystems. On the international level, another challenge for the G20 is the coordination of national economic policies in order to create global conditions for sustainable economic development. Because of differing interests, economic structures and economic situations among the individual G20 countries, a coordination of economic policies will be difficult to achieve, as shown by the experiences in the areas of global macreconomic imbalances and currency policy. However, the G20 should address the global economy's big challenges, in order to jointly solve at least some of its problems.
Keywords: 330